Increased Percentage of CD8+CD28− Regulatory T Cells With Fingolimod Therapy in Multiple Sclerosis. Issue 2 (19th March 2023) - Houston, Timothy W.; Howlett-Prieto, Quentin; Regenauer, Colin; Testai, Fernando D.; Yao, Faith; Feng, Xuan; Reder, Anthony T.
Abstract : Background and Objectives: Fingolimod, an oral therapy for MS, decreases expression of membrane S1P1 receptors on CD4 + memory cells, causing their retention and deactivation in lymph nodes. We determined fingolimod effects on the number and proportion of potentially CNS-damaging CD8 + CD28 + cytolytic T lymphocyte cells (CTLs) and on MS-depleted and dysfunctional CD8 + CD28 − anti-inflammatory suppressor/regulatory T cells (Treg) and on CD8 + T-cell expression of the CD69 activation/lymph node retention protein in MS. Methods: CD8, CD28, CD4, and CD69 expression on peripheral blood mononuclear cells was measured with flow cytometry. In vitro concanavalin A (ConA) activation of T cells, including CD8 + CD28 − cells, was used to mimic inflammation. Results: Fifty-nine patients with MS, 35 therapy-naive (16 clinically stable; 19 exacerbating) and 24 fingolimod-treated (19 clinically stable; 5 exacerbating), and 26 matched healthy controls (HCs) were compared. In therapy-naive patients, the CD8 + Treg percent of total lymphocytes was only 1/4 of HC levels. In fingolimod-treated patients, however, CD8 + Treg percentages rose to 2.5-fold higher than in HC and 10-fold higher than in therapy-naive MS. With fingolimod therapy, in contrast, CD8 + CTL levels were less than half of levels in HCs and therapy-naive patients. In HCs and all MS, activation with ConA strongly induced CD69 expression on CD4 + cells and induced 3-fold higher CD69 levels on CD8 + CTL than on CD8 + Treg. Fingolimod and analogs in vitro did not modify lymphocyte CD69 expression. Lower levels of CD69 on CD8 + Treg than on CTL may allow easier Treg egress from lymph nodes and enhance control of peripheral inflammation. In vitro activation reduced the already low CD8 + Treg population in therapy-naive MS, but only slightly altered Treg levels in fingolimod-treated MS. Discussion: Fingolimod therapy markedly increases the percentage of CD8 + Treg in MS, reversing the low CD8 + Treg:CTL ratio seen in untreated MS. The increase in immune regulatory cells has potential therapeutic benefit in MS. Activation in vitro depletes CD8 + CD28 + CTL in patients with MS; the loss is more pronounced in older patients with MS. This suggests that inflammation can disrupt the tenuous immune regulation in MS, especially in older patients.